(untitled) (-, 2013)
" " 1994 . . (10) (212) . : 1) . 2) . 3) .
Keywords: Evangelical School; Formation continue des enseignants; Gestion scolaire; Leadership; Leadership Evangelical School; Private sector; Secteur Privé; Teachers in-service training School management